2021
DOI: 10.31557/apjcp.2021.22.4.1305
|View full text |Cite
|
Sign up to set email alerts
|

The Apoptotic Properties of Leaf Extracts of Simarouba glauca against Human Leukemic Cancer Cells

Abstract: more than 170 species of trees and bushes of pantropical distribution (Alves et al., 2014). Its common names are Lakshmi Taru and paradise-tree. A molecular phylogeny of the family was reported in 2007, data revealed with the relationships within the family (Clayton et al., 2007).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In the present study, it is strongly suggested that the markedly elevated WBC counts, lymphocytes and monocytes differentials observed at varied doses may not be unconnected with cellular in ammatory responses elicited by inherent phytochemicals of the leaf extracts of S. glauca [17,25,34], which may have signaled, stimulated and activated the release of T-helper cells, macrophage colony stimulating factor, interleukins IL-2 IL-4 and IL-5, proliferation, differentiation and maturation of committed stem cells responsible for the production of white blood cells and differentials [35,36].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In the present study, it is strongly suggested that the markedly elevated WBC counts, lymphocytes and monocytes differentials observed at varied doses may not be unconnected with cellular in ammatory responses elicited by inherent phytochemicals of the leaf extracts of S. glauca [17,25,34], which may have signaled, stimulated and activated the release of T-helper cells, macrophage colony stimulating factor, interleukins IL-2 IL-4 and IL-5, proliferation, differentiation and maturation of committed stem cells responsible for the production of white blood cells and differentials [35,36].…”
Section: Discussionmentioning
confidence: 56%
“…The stem-bark and leaf extracts of S. glauca contain triterpenes, useful in curing amoebiasis, diarrhea and malaria [15]. Chemicals present in leaf, fruit, pulp and seed of S. glauca have been reported to possess analgesic, anticancer, antimicrobial, antiviral, astringent, cardio-protective, emmenagogue, stomachic, tonic, vermifuge properties [15][16][17][18]. The present study focused on the toxicological evaluation of leaf extracts of S. glauca on some selected hematological indices of male Wistar rat Materials And Methods Collection of S. glauca leaves and preparation of Extracts Leaves of S. glauca were collected from Cercobela Farms®, Ubiaja, Esan South East Local Government Area of Edo State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%